The African wife of Joseph, Asenath (Gn 41:45, 41:50, 46:20) - Adamo, David Tuesday (Journal for semitics, 2013)
Passages that refer to women in general are not well dealt with in critical discussion. Passages that mention the presence and contribution of African women in the Bible are somehow more neglected; perhaps (1) there are few women African biblical scholars; (2) the deep prejudices against African women brought about the negligence or inadequate critical discussion on biblical passages with references to women generally. The passages on the African wife of Joseph, Asenath, are so scanty in the Bible (Gn 41:45, 50 and 46:20) that very few critical biblical scholars have noticed them. The main purpose of this article is to discuss the presence and the contribution of the African wife of Joseph mainly in the biblical tradition and the implication and challenges to Israel and to modern society. References will not only be to the Bible alone but also to the apocryphal literature, midrashic commentaries, Greek, and Islamic traditions.